Food waste behaviors of the families of the Cilento Bio-District in comparison with the national data: elements for policy actions - Di Veroli, Jacopo Niccolò; Peronti, Benedetta; Scognamiglio, Umberto; Baiamonte, Irene; Paoletti, Flavio; Stefanovic, Lilliana; Bügel, Susanne Gjedsted; Aboussaleh, Youssef; Średnicka-Tober, Dominika; Rossi, Laura (Frontiers in Sustainable Food Systems, 2024)
Introduction Consumer food waste at the household level results from a complex set of behaviors depending on the local food environment, among other factors. This study mainly aimed at comparing food waste behaviors in the Cilento Bio-District with those recorded at the national level to explore if the organic district model had an impact on food waste attitude as a sustainability element. Methods Household food waste behavior indicators performed better at the national level than in the Cilento Bio-District, with some relevant exceptions, such as the avoidance of having too much food at home and impulse buying. Results The study results suggest that some food waste attitudes in the rural community of the Bio-District might be so embedded in everyday practices that they are no longer perceived as relevant descriptors, considering the lower food waste (FW) levels in Cilento compared to national data. The key findings of the study were interpreted for policy action development. Discussion The overall priority of actions would be the enhancement of consumers’ abilities to impact practices for food waste prevention. Community engagement aspects and the local products’ promotion should be particularly pursued in the Cilento Bio-District, while broader policy actions were proposed at the national level with the involvement of the different sectors of the food chain and the proposition of regulatory aspects (e.g., labels). Future research on Cilento Bio-District characteristics and the comparison with national data would need a more comprehensive examination of additional factors affecting the food system, such as dietary patterns or organic product consumption, to understand their potential influence on food waste and, in general, the sustainability of food choices.